Can Ex-Parliamentarians Tell Political Counter-Narratives? - Hyvärinen, Matti (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2024)
Telling counter-narratives has sometimes been exclusively reserved for marginal and minority groups. This article asks, instead, whether such elite group members as veteran parliamentarians will also tell counter-narratives in their oral history interviews. When the telling of counter-narratives is understood as a communicative strategy, open to various actors, the decisive question concerns about how to recognize these narratives. Previous literature provides such criteria as the stance toward some other narratives and illocutionary intent, which are helpful but not yet decisive. This article suggests that the limits of counter-narrative are and will remain negotiable since there is no easily recognizable participant orientation or speech act of telling a counter-narrative. This article proceeds to study empirically the possible markers of narrative countering.